Between national socialism and Soviet communism : displaced persons in postwar Germany - Holian, Anna Marta (Social history, popular culture, and politics in Germany, 2011)
The invention of the displaced person -- Displaced persons and the question of persecution -- The repatriation debate and the anticommunist "political explanation" -- Between federalists and separatists : the anticommunist movement(s) -- Jewish survivors and the reckoning with the Nazi past -- Displaced Jews and the German question -- Political prisoners and the legacy of national socialism -- Recognition, assistance, Wiedergutmachung : the claims of displaced politicals